Voices of the participants: The selling of popular culture at Wounded Knee. - Gabrielle Ann Scott Elliott; Lisa Pollard (Adult Education Research Conference, 1997)
Popular culture narratives surrounding the Occupation of Wounded Knee have worked to neutralize the significance of the acts of resistance by participants, particularly women.